Penguatan Manajemen Personalia: Tantangan Guru dalam Mengelola Pembelajaran di SLB A Yaketunis - Ratna Putri Pradita; Qo-idah Ariq Pangesti; Anugrah Ainul Yakin; Difa’ul Husna (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Special School (SLB) A Yaketunis is a special school for children with special needs. Teachers at this SLB face various challenges in managing learning. The aim of this research is to analyze the challenges faced by teachers in managing learning at SLB A Yaketunis as well as efforts to strengthen personnel management as a solution. This research uses a qualitative approach. The research results show that the main challenges faced by teachers include limited student abilities, lack of supporting facilities and infrastructure, and excessive teacher workload. To overcome these challenges, schools need to strengthen personnel management starting from planning teacher needs, appropriate recruitment and selection, training and professional development of teachers, to regular evaluation of teacher performance. By strengthening personnel management, it is hoped that it can improve the quality of learning and the welfare of teachers at SLB A Yaketunis.